(untitled) (CIPEEX, 2024)
The management and control of psychotropic medications constitute a crucial area of pharmaceutical practice, requiring not only technical competence but also a deep understanding of the complexities involved. These compounds, often prescribed to treat psychiatric conditions such as psychotic disorders, have properties that directly affect the central nervous system. From this perspective, the pharmacist plays an essential role in promoting mental health, ensuring treatment adherence and safety, and contributing to better outcomes. Additionally, guidance and education on the long-term use of psychotropics are fundamental to preventing chemical dependency and improving patients’ quality of life. To investigate the role played by pharmacists in the management of medications for patients affected by mental disorders.This is a literature review conducted using scientific articles available on digital platforms such as SCIELO and the Virtual Health Library. The research was carried out during July of this year, employing a search strategy with the following descriptors: “mental health, pharmacist, and management of psychotropic medications.” Inclusion and exclusion criteria were applied to select articles published in the last five years, with no language restrictions. Initially, titles and abstracts of identified articles were evaluated. Those deemed relevant to the topic were selected for the review, resulting in a total of 4 articles included in the analysis. The data presented highlights the essential role of the pharmacist in promoting and preventing health, as they are crucial in the treatment of mental illnesses. Their competence in managing adherence, maintenance, and control of medications is necessary for effective medication therapy. Pharmacists provide guidance, education, and personalized support to patients, clarifying medication details, assisting in understanding schedules, dosages, and side effects, and helping manage any adverse effects. Pharmaceutical care is an essential aspect of mental health support. Pharmacists can influence treatment adherence by helping to plan therapeutic routines, addressing doubts and insecurities, and identifying and alerting patients to potential interactions pharmaceutical care makes the process more human and safe. The pharmacist can explain to the patient the need for and benefits of the medication, highlighting how it can improve their clinical condition. Additionally, they should clarify that side effects may occur but are often part of the process. It is crucial that the patient does not stop taking the medication to avoid worsening the treatment.